Synthesis and characterization of isodecyl methacrylate monomer and its copolymer with acrylamide for oil/water separation (Samarra Journal of Pure and Applied Science, 2026)
In this work, isodecyl methacrylate monomer IDMA was synthesized by esterfication of methacrylic acid with isodecylalcohol. IDMA monomer was then copolymerized with acrylamide monomer AAM, in different feed compositions, using free radical polymerization technique. The synthesized IDMA and IDMA/AAM copolymer were characterized by employing proton nuclear magnetic resonance and Fourier transform infrared spectroscopy techniques. Composites of fabricated polymers with metallic mesh, having different pore size, were prepared to examine their performance for separation oil from water. Separation time, reclaimed oil, coating percentage with polymer, and water recovery were directly affected by the composition of copolymer and mesh pore size. Microscopic and photographic images of water, before and after separation by polymers, showed that oil was completely removed from water.